Strange strangers: The Jerusalem correspondents in the network of nations. (August 2016) - Bourdon, Jérôme
This research is based on an ethnographic investigation of foreign press correspondents working in Israel–Palestine. It strives to understand how the work of these correspondents is linked to a network of changing and overlapping collective identities, be they national or ethnic, for both journalists and their audiences. This is analyzed at three levels: (1) just as the Western world is politically divided in respect to this conflict, so too is the journalistic world, where suspicion of pro-Palestinism or pro-Israelism is voiced, albeit mezza voce or off the record; (2) the journalists feel professionally challenged when their impartiality is questioned due to their own religious or ethnic identities; and (3) finally, audiences have changed, through a revival of ethnic and religious identities, overlapping political involvement in the conflict, and technology which makes surveillance and 'media monitoring' much easier. This form of 'diasporic nationalism' puts increasing pressure on journalists.